Psychosocial Factors at Work in the Asia Pacific 2014
DOI: 10.1007/978-94-017-8975-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Culture and Bullying; Personal Accounts of Workers in Malaysia

Abstract: Workplace bullying has been termed the cancer of the workplace; it is a widespread and often intractable problem. Internationally, a wealth of research has examined the prevalence of workplace bullying and its negative effects. This research base and the scientific definition of workplace bullying are, however, based on Western perspectives and supported by theories, models, and research studies conducted in Western

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Finally, though care was taken to identify potential confounders from the literature and adjust each association accordingly, residual confounding may still be an issue. Though we had adjusted for sociodemographic, employment, and individual trait characteristics, other factors that have been linked to workplace bullying such as social, coping and problem‐solving skills, organisational change, and societal norms and culture were not able to be included in this study due to limited resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, though care was taken to identify potential confounders from the literature and adjust each association accordingly, residual confounding may still be an issue. Though we had adjusted for sociodemographic, employment, and individual trait characteristics, other factors that have been linked to workplace bullying such as social, coping and problem‐solving skills, organisational change, and societal norms and culture were not able to be included in this study due to limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings generate hypotheses that could be tested in more robust studies such as longitudinal studies to enable the ascertainment of cause‐and‐effect. Future studies examining workplace bullying among junior doctors may also focus on variables linked to workplace bullying that were not examined in this study, including psychological capital, social, coping and problem‐solving skills, conflict management styles, core self‐evaluations, organisational change, and societal norms and culture . In addition, supplementing quantitative findings with qualitative findings and considering the perpetrators' perspectives may allow for a more holistic and comprehensive understanding of the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace bullying is an emerging concept in Malaysia too. Bullying is reported by Kwan et al [6] as part of the dominant culture of Malaysian organisations. Employees feel pressure to acquiesce to bullying situations because such behavior represents power and authority within the organisation.…”
Section: Workplace Bullying In Eastern Countriesmentioning
confidence: 96%
“…Eastern-based research has revealed different notions of bullying. Malaysian employees view bullying, particularly work-related bullying behaviors, as common and expected-a form of institutionalised mistreatment based on the power hierarchy in Malay culture, and physical intimidation is not a factor [6]. Likewise, Loh, Restubog, and Zagenczyk [7] argued that Eastern employees perceive workplace bullying as a common practice that forms part of the organisational culture.…”
Section: Introductionmentioning
confidence: 99%
“…If so, workplace bullying would be expected to be more common in African and some Asian societies in comparison with European countries. For instance Malaysia ranks high in power distance and low in uncertainty avoidance, and the country reports high levels of workplace bullying at the corporate level (Kwan, Tuckey, & Dollard, 2014). Accordingly, to understand workplace bullying, it is necessary to also take into account the cultural context in which it occurs.…”
Section: Cultural Differences In Workplace Bullyingmentioning
confidence: 99%